Exploring Simmel's Social Types in Kemal Tahir's Novels: A New Perspective on Turkish People - Özge Seda Uğraş; Mehmet Uğraş (Selçuk Üniversitesi Edebiyat Fakültesi Dergisi)
Kemal Tahir is a significant novelist who witnessed a critical era, from the late Ottoman Empire to the early years of the Turkish Republic, a time when social and political realities were being transformed. The period he experienced continuous to have sociological, political, and socio-economic impacts that persist to this day. Consequently, his observations on Turkish society remain relevant in many respects. He continues to be an influential intellectual, offering an alternative interpretation of official historiography by blending literature, history, and sociology. His handling of events, versatility, and original perspectives provide readers with unique insights. This study examines seven books by Kemal Tahir between 1955-1980. These books, recently republished in chronological order by Ketebe Publications in 2022 under the series called "1890-1945 Turkey," include; A Castle of Property (Bir Mülkiyet Kalesi), Tired Warrior (Yorgun Savaşçı), People of the Captive City (Esir Şehrin İnsanları), Prisoner of the Captive City (Esir Şehrin Mahpusu), Wolf Law (Kurt Kanunu), Crossroad (Yol Ayrımı), and The Seed in the Steppe (Bozkırdaki Çekirdek). The study focuses on Kemal Tahir's seven novels, totaling over three thousand pages, and the author's characteristics which can be viewed as ‘social types’ representing Turkish people and society. Drawing on Georg Simmel's conceptual framework of social types, the study aims to explore how Kemal Tahir's depiction of characters reflects broader societal norms and values. Additionally, it seeks to analyze the political and cultural influences that motivated Tahir to write these novels and their impact on the construction of social life.